(untitled) (Gaceta Técnica, 2018)
This paper discusses the flexural strength of reinforced concrete beams of square cross section, exposed to fire during different times. After being exposed to fire the beams were left to cool at room temperature for 24 hours, the changes produced by this phenomenon were evaluated by observation. The temperatures reached oscillated between 750 °C and 1050 °C. Through the ASTM C78 test it was determined that the flexural strength decreases drastically as the temperature and exposure time of the beams increases, showing different signs of degradation ranging from a slight calcination and change of coloration to the loss of section of the element. This research showed that the flexural strength decreased by more than 90% with respect to the beams not exposed to fire, this result was obtained when a temperature of 1050 °C was reached at 180 minutes of exposure to fire